A new method for risk assessment in industrial processes. Issue 19 (2022) - Falcone, D.; Bona, G. Di; Forcina,
Abstract: Safety is one of the most important issues in modern industrial plants and industrial activities. The Safety Engineering role is to ensure acceptable safety levels of production systems, not only to respect local laws and regulations, but also to improve production efficiency and to reduce manufacturing costs. For these reasons the choice of a proper model for risk assessment is crucial. In this context, the present research aims to propose a new method, called Total Efficient Risk Priority Number (TERPN), able to classify risks and identify corrective actions in order to obtain the highest risk reduction with the lowest cost. The main scope is to suggest a simple, but suitable model for ranking risks in a company, to reach the maximum effectiveness of prevention and protection strategies. The TERPN method is an integration of the popular Failure Mode Effect and Criticality Analysis (FMECA) with other important factors in risk assessment.